Coercion, Violation of Privacy and Everyday Difficulties as the Cause of Patient Refusal Treatment in Psychiatric Hospitals in Russia - K. Rzhevskaya, Natalia; A. Ruzhenkov, Viktor; V. Ruzhenkova, Victoria; S. Moskvitina , Ulyana; A. Kolosova, Marina (International Journal of Criminology and Sociology, 2022)
Treatment in a psychiatric hospital is accompanied by a restriction of independence, violation of privacy, coercion, which causes displeasure of patients. The aim of the study was to verify the scale of everyday problems, violations of privacy and coercion in a psychiatric hospital to develop recommendations for the organization of a therapeutic environment. The study included 191 patients in a psychiatric hospital. Anonymous questionnaire was used. Statistical processing of the database was carried out by nonparametric methods. The majority of patients (67%) estimated the conditions of stay in a psychiatric hospital at 7-10 points (10-point scale), but half of them complained about the need for self-purchase of drugs. A full night's sleep was disturbed by the snoring of others (56.5%), an uncomfortable bed (36.6%), bright light (26.2%). The poor diet was indicated by 45.5% of patients. Patients indicated coercion by medical staff: retention (11.5%), forced administration of drugs (12%), coercion to consent to treatment (22%), refusal to discharge from hospital (35.1%). It was reported that there was a violation of privacy in the toilet (36.6%), difficulties to observe the intimate hygiene (16.8%). These problems caused patients to refuse inpatient treatment if there was the possibility of outpatient treatment (65.2% of men and 52.6% of women). Despite the low level of claims of patients to living conditions, it is important to respect their rights in psychiatric hospitals to privacy, creating a comfortable living space, the organization of differentiated methods of observation by medical staff.